Systemic evaluation of febrile thrombocytopenia - Katiyar, Vivek; Khare, Rajesh (International Journal of Advances in Medicine, 2018)
Background: Febrile patient with thrombocytopenia is commonly encountered by physicians especially during monsoon and perimonsoon period. Infections with protozoa, bacteria and viruses can cause thrombocytopenia with or without disseminated intravascular coagulation. Commonly dengue, malaria, scrub typhus and other rickettsial infections, meningococci, leptospira and certain viral infections present as fever with thrombocytopenia. Occasionally these patients can go on to develop a stormy course with multiorgan dysfunction requiring intensive care unit admission associated with high morbidity and mortality. Though thrombocytopenia is encountered in various diseases, it is for sure that potentially fatal bleeding due to thrombocytopenia is rare. The study was intended to know the underlying etiology of febrile thrombocytopenia in our community, the various presentations and relationship between platelet level and severity of disease and prognosis. Methods: This study was carried out in 218 adult patients (age above 18 years) presenting with fever having thrombocytopenia (platelet count <1,50,000/mm3) in Dept. of medicine in IIMS and R Lucknow UP. Results: Dengue was the commonest cause of fever with thrombocytopenia (58.71%) followed by P. falciparum malaria 8.71% and P. vivax malaria 6.88%. Bleeding manifestations were seen in 24.31% of patients. 58.49% of patients had patechie/purpura as the commonest bleeding manifestation followed by hematuria in 16.98 %. Conclusions: Fever with thrombocytopenia consists of occult presentations of common diseases rather than rare disease. Infection is the commonest cause of fever with thrombocytopenia. Among infections, dengue was the commonest cause. Treatment of underlying condition will lead to rapid improvement in platelet count with complete clinical recovery.